PENGAWASAN LIMBAH MEDIS BAHAN BERBAHAYA DAN BERACUN RUMAH SAKIT UMUM DAERAH SELASIH KABUPATEN PELALAWAN - Rahma Datul Uska; Harapan Tua RFS (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Pelalawan Regency is one of the districts in Riau Province which has been growing rapidly in recent years, one of which is improving health services with the Healthy Pelalawan Strategic Program. Selasih Regional General Hospital Pelalawan District is a hospital owned by the Regional Government of Pelalawan District which has an important role as a front guard in supporting the Healthy Pelalawan  Strategic Program which has the most complete specialist doctors and has become a basic level accredited Regional Service Agency. But the Hospital does not yet have an incinerator permit from the Ministry of Environment to manage its own waste, so that when the Environmental Agency of Pelalawan Regency carried out the Supervision of the Implementation of Environmental Permits on 5 November 2018 there were still some shortcomings and not yet in accordance with the regulations stipulated in the management of hazardous and toxic material waste. The purpose of this study was to find out how to monitor medical waste of the Selasih Regional General Hospital carried out by the Environmental Agency of Pelalawan Regency and the inhibiting factors in the supervision. The concept of the theory used is the Manullang Supervision theory, namely: Establishing a Measuring Instrument (standard), Conducting Evaluation and Conducting Corrective Action. This study uses a qualitative research method with a descriptive approach by using Purposive Sampling techniques with data collection techniques including: interview, observation, literature study and documentation. The results of this study indicate that the supervision of medical waste toxic and hazardous waste in the Selasih Regional General Hospital conducted by the Environmental Agency of Pelalawan Regency is not optimal. Inhibiting factors include budget, human resources and society participation. It is better if the Environmental Agency of Pelalawan Regency increases the intensity of supervision to prevent environmental pollution. * Keywords : Supervision, Medical Waste, Hazardous and Toxic Materials